The Effect of Evidence-based Education on Self-care Behaviors in Patients with Congestive Cardiac Failure: A Clinical Trial Study - Rokhzadi, Mohammadzahed (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objective: Heart failure is a chronic and disabling disease that continues to increase despite medical advances. One of the important and non-pharmacological strategies to improve clinical outcomes in these patients is to promote self-care behaviors using the latest scientific evidence. Therefore, the objective of this study is to determine the effect of evidence-based education on self-care behaviors in patients with congestive cardiac failure. Materials and Methods: This clinical trial was performed on 104 patients in the coronary care unit (CCU) and post-CCU ward of Imam Khomeini Hospital in Islamabad, Iran, in 2016. The qualified patients were randomly divided into two groups: Control and intervention groups. Initially, a pre-test was performed on both the groups. Patients in the control group receive routine education. Patients in the intervention group received three education sessions that were prepared based on the latest scientific evidence. After 2 weeks, the patients were followed-up with phone on observing self-care behaviors. After a month, the questionnaire was completed by control and intervention groups. Results: The mean (standard deviation [SD]) of scores in the first and second-order control groups were respectively equal to 41.44 (4.17) and 41.34 (4.3) and the mean (SD) in the intervention group before and after education were equal to 42.73 (4.37) and 30.86 (3.7). Paired t-test showed a significant difference between the intervention group before and after education (P value = 000). However, the group did not find any significant difference in the control group (P value = 0.364). A significant level of P < 0.05 was considered. Conclusion: Evidence-based education can be used as an effective educational method for improving self-care behaviors in patients with heart failure.